Growth and development in emerging market economies international private capital flows, financial markets and globalization - Kohli, Harinder S. 1945- (SAGE, 2008)
This book addresses senior policy makers interested in understanding & debating key issues currently faced by the better performing emerging markets throughout the world. Papers in the volume address international capital flows, financial markets, globalization & private participation in infrastructure development